Developing a genomics rotation: Practical training around variant interpretation for genetic counseling students. Issue 2 (1st February 2019) - Grove, Megan E.; White, Shana; Fisk, Dianna G.; Rego, Shannon; Dagan‐Rosenfeld, Orit; Kohler, Jennefer N.; Reuter, Chloe M.; Bonner, Devon; ,; Wheeler, Matthew T.; Bernstein, Jonathan A.; Ormond, Kelly E.; et al.
Abstract: With the wide adoption of next‐generation sequencing (NGS)‐based genetic tests, genetic counselors require increased familiarity with NGS technology, variant interpretation concepts, and variant assessment tools. The use of exome and genome sequencing in clinical care has expanded the reach and diversity of genetic testing. Regardless of the setting where genetic counselors are performing variant interpretation or reporting, most of them have learned these skills from colleagues, while on the job. Though traditional, lecture‐based learning around these topics is important, there has been growing need for the inclusion of case‐based, experiential training of genomics and variant interpretation for genetic counseling students, with the goal of creating a strong foundation in variant interpretation for new genetic counselors, regardless of what area of practice they enter. To address this need, we established a genomics and variant interpretation rotation for Stanford's genetic counseling training program. In response to changes in the genomics landscape, this has now evolved into three unique rotation experiences, each focused on variant interpretation in the context of various genomic settings, including clinical laboratory, research laboratory, and healthy genomic analysis studies. Here, we describe the goals and learning objectives that we have developed for these variant interpretation rotations, and illustrate how these concepts are applied in practice.